Scope for Post Harvest Management in North East India through Zero Energy Cool Chamber - Devi, S. Roma; Singh, L Kanta (Indian Journal of Hill Farming, 2016)
To reduce the problems of post harvest losses at farmer level, Zero Energy Cool Chamber (ZECC) system of storage was taken for study for storage of vegetable and fruits at Wokha district of Nagaland and Imphal West district of Manipur. It is eco friendly and zero energy requirements for storage of vegetables and fruits. ZECC improves the quality and productivity of vegetables and fruits by reducing field heat, increasing shelf life and checking post harvest losses respectively. The study in Wokha, Nagaland found that shelf life of cucumber was 18 days in ZECC condition and as in room condition it was 13 days and weight loss was 33.3% and 33.5% respectively. Shelf life of French bean was same for both in ZECC condition and room condition, but weight loss was 15.0% in ZECC condition and 33.3% loss in room condition. In case of passion fruit it was 9 days for ZECC condition and 5 days for room condition and weight loss was found to be 6.7% and 8.3% respectively. The study in Imphal West, Manipur revealed that Shelf life of cabbage was 10 days in ZECC condition and 4 days in room condition. Storage duration of cauliflower was found 15 days under ZECC condition and 6 days under room condition. Shelf life of mushroom under ZECC condition was 5 days and one day under room condition. There is big scope for study for storage of different vegetables and fruits for different region and its suitability by using Zero Energy Cool Chamber storage system.